Calling in the heat: the zebra finch "incubation call" depends on heat but not reproductive stage. (8th October 2018) - McDiarmid, Callum S; Naguib, Marc; Griffith, Simon C
Abstract : It was recently suggested that in hot conditions captive zebra finches make a call ("incubation-call" or "v-call") during late egg incubation so their offspring develop to be more heat-adapted. Here, we confirm that in the wild v-call production increases with temperature. However, parents with freshly-laid eggs or chicks also produced v-calls, as did nonbreeding captive birds. This is unlikely to be a specifically evolved "incubation call, " but may instead be a general response to heat. Abstract: Environmental conditions during early development can profoundly impact an organism's phenotype, potentially resulting in future adaptations. Offspring can often obtain environmental information directly, but in some cases rely on parental cues or signals. It was recently suggested that at high ambient temperatures zebra finch ( Taeniopygia guttata ) parents use acoustic signals ("incubation calls" or hereon "v-calls") to adaptively alter offspring development for hot conditions. However, this conclusion requires a thorough understanding of the timing and production of the call. In this study, we use audio recordings (1696 h) from within wild zebra finch nest-boxes, and of nonbreeding captive zebra finches experimentally exposed to heat, to characterize the circumstances under which v-calls are produced. V-call incidence was positively related to ambient temperature in the wild and captivity, confirming that v-calls are temperature dependent. However, v-calls were not limited to late incubation (as previously suggested) and were instead produced throughout incubation and chick rearing in the wild, and by nonbreeding captive adults. Videos of the captive birds revealed that v-calls were produced during "bouts" of panting. We found no evidence that during v-call production breathing patterns were being altered from that optimal for panting and typical of quiet respiration (1:1 inspiration:expiration). While embryos may gather climatic information from this heat-related call, it is produced over a range of conditions so is unlikely to be a specifically evolved signal for offspring programming. The idea that parents use specifically evolved signals to provide offspring with climate information requires further study.